2019
DOI: 10.1002/slct.201901689
|View full text |Cite
|
Sign up to set email alerts
|

Chronoamperometric Detection of Amoxicillin at Graphite Electrode using Chelate Effect of Copper(II) Ions : Application in Human Blood and Pharmaceutical Tablets

Abstract: A novel electrochemical method is suggested for indirect chronoamperometric determination of amoxicillin (AMX) in the presence of copper ions Cu (II) at carbon paste electrode (CPE). The method is based on the interaction between the β-lactam antibiotic and copper ions. This interaction was firstly studied by square wave voltammetry (SWV), where the peak corresponding to the oxidation of AMX at 0.7 V decreases significantly in the presence of copper ions. The reaction product is characterized by UV-visible spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It presents an oxidation peak at 0.8 V attributed to the oxidation of OH group of the phenolic sites of AMX (φ-OH). 30 The mechanism of the electrochemical oxidation of AMX is 22 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It presents an oxidation peak at 0.8 V attributed to the oxidation of OH group of the phenolic sites of AMX (φ-OH). 30 The mechanism of the electrochemical oxidation of AMX is 22 :…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] In our previous work, we reported that the electrochemical behavior of AMX is influenced by the presence of certain metal ions. 22 This motivated us to conduct an in-depth study to elucidate the effect of metal ions such as Cu(II), Zn(II), Fe(III) on the electrochemical behavior of AMX.…”
mentioning
confidence: 99%